Pendekatan Failure Effect Analysis (FMEA) dalam Analisis Risiko Produksi Padi: Studi di Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Raesi, Syahyana; Putri, Afrianingsih; Sinensis, Vradelmeika (Universitas Galuh, 2026)
Ranah Pesisir District is ranked third as the largest rice producing area in Pesisir Selatan Regency which experiences fluctuations in production. Fluctuations indicate risks, one of which is production risks such as human resources, pests and diseases, facilities and infrastructure, and natural disasters. The research objective is to identify sources of production risk, measure the level of production risk and formulate production risk management. The method used in this research is a quantitative method with a sample of 43 rice farmers taken using proportional sampling in Ranah Pesisir District. Next, the data was analyzed using fishbone diagrams and FMEA (Failure Mode Effect Analysis). The research results based on the calculation of the RPN (Risk Priority Number) value show 7 priority risk sources from the 14 identified risk sources. Risks that must be prioritized. The first priority risk is bed bugs with an RPN value of 18.81, the second is insufficient water with an RPN value of 17.28, the third is damaged irrigation channels with an RPN value of 11.74, the fourth is grasshoppers with an RPN value of 9.19, the fifth is late planting seeds with an RPN value of 9.13, the sixth is cattle with an RPN value of 8.58 and the seventh is sting grasshopper with an RPN value of 8.32.